2019
DOI: 10.17265/1548-6648/2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotyping in Saudi Population

Abstract: Background: Hepatitis C is one of the common types of viral hepatitis that threatens human life worldwide. Hepatitis C virus (HCV) is a single-strand RNA virus that has the ability to be transmitted by contaminated blood products and intravenous drug use. HCV is characterized by its ability to have a high genetic diversity, which eventually results in different HCV genotypes and numerous subtypes; however, this genetic variety is a core reason for the lack of a successful vaccine for these types of viruses. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Variations in genotype prevalence present challenges to the development of vaccines and therapeutics. The geographic distribution of HCV genotypes varies, and the transmission mode may influence the dominance of specific genotypes [3,12]. The study demonstrated the difference in the distribution of hepatitis C virus genotypes between the age groups of patients 50 years and older and less than 50 years.…”
Section: N Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Variations in genotype prevalence present challenges to the development of vaccines and therapeutics. The geographic distribution of HCV genotypes varies, and the transmission mode may influence the dominance of specific genotypes [3,12]. The study demonstrated the difference in the distribution of hepatitis C virus genotypes between the age groups of patients 50 years and older and less than 50 years.…”
Section: N Discussionmentioning
confidence: 87%
“…In this study, most chronically HCV-infected individuals were infected with GT-2 and GT-4 (33.1% and 25.8%), respectively. In Saudi Arabia, GT-4 was cited as the most common HCV genotype [2,9,12]. In addition, few studies reported a high prevalence of GT-4 across Saudi Arabia [2,9,12].…”
Section: N Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Genotypes 1 and 4 are responsible for 86% of chronic HCV infections in Saudi Arabia. [19][20][21] HCV is primarily transmitted through exposure of infected blood. 22 Unsafely performed injection practices is the most predominant mode for transmission and it accounts to 40% of HCV infections reported worldwide.…”
Section: Introductionmentioning
confidence: 99%